An overview; consecutive periods in cocaine use disorders - Şatır, Tulga Tolun; Kalyoncu, Ayhan; Pektaş, Özkan (Journal of Dependence, 2000)
Coca in Use Disorders have two consecutive periods as abuse and abstinence. There are biological, psychological and social differences between two periods. Laboratory and clinical studies on these two periods inform us new developments can be seen in the tretment of Cocaine Use Disorders.
Keywords: cocaine; dependency; substance